2020
DOI: 10.1093/hmg/ddaa046
|View full text |Cite
|
Sign up to set email alerts
|

CNS glycosylphosphatidylinositol deficiency results in delayed white matter development, ataxia and premature death in a novel mouse model

Abstract: The glycosylphosphatidylinositol (GPI) anchor is a post-translational modification added to approximately 150 different proteins to facilitate proper membrane anchoring and trafficking to lipid rafts. Biosynthesis and remodeling of the GPI anchor requires the activity of over 20 distinct genes. Defects in the biosynthesis of GPI anchors in humans lead to inherited glycosylphosphatidylinositol deficiency (IGD). IGD patients display a wide range of phenotypes though the central nervous system (CNS) appears to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…None of the mutants survived past weaning, with 50% hemizygous cko not surviving 2 days after birth and 50% of mosaic cko not surviving 19 days after birth. The brain size of mutants was smaller than that of WT ( 18 ). In the current study, we used Emx1-Cre , Vgat-Cre and Pkcd-Cre mouse lines to target ablation to telencephalon excitatory neurons, inhibitory neurons and thalamic neurons, respectively.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…None of the mutants survived past weaning, with 50% hemizygous cko not surviving 2 days after birth and 50% of mosaic cko not surviving 19 days after birth. The brain size of mutants was smaller than that of WT ( 18 ). In the current study, we used Emx1-Cre , Vgat-Cre and Pkcd-Cre mouse lines to target ablation to telencephalon excitatory neurons, inhibitory neurons and thalamic neurons, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…All of the mosaic mutants and thalamus-specific hemizygous mutants (Th-H-cko) could survive as long as control mice, at least for 1 year. These data suggested that the short life span in Nestin-Cre -induced Piga mosaic mutants (Nestin-M-cko) ( 18 ) was more likely due to the deficits of GPI anchors in non-neuronal cells including astrocytes and oligodendrocytes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Piga flox mouse line, three loxP sites with identical orientation were inserted within the Piga gene on X chromosome, with one loxP localized in intron 5 and the other two loxP sites flanking a Neo gene localized downstream of exon 6 (Fig1.A). Previous work using this mouse line proved that deletion of exon 6 upon Cre recombination resulted in an efficient ablation of Piga and disrupted the cell surface expression of GPI-APs (16)(17)(18)20). Our In situ hybridization on adult mouse brain showed that Piga is widely expressed in almost all the neurons, and has a very strong expression in CA1 pyramidal cells and dentate gyrus (DG) granule cells of the hippocampus, and piriform cortex (Fig1.B).…”
Section: Generation Of Different Neuronal Population-specific Piga Ckmentioning
confidence: 99%
“…These mutated mice showed deficits in cerebellar and white matter development, ataxia and tremor, and did not survive past weaning. The early lethality of these mice exclude the possibility to examine their cognitive and epileptic phenotype thoroughly (18). In addition, Nestin is also expressed in a variety of tissues and progenitor cells, including pancreatic islets , skeletal muscle satellite cells, developing myotomes, testis, hair follicle, heart, and the non-hematopoietic fraction of the bone marrow (19), further adding to the complexity of explaining the mutants' phenotype.…”
Section: Introductionmentioning
confidence: 99%